2020
DOI: 10.1136/ijgc-2019-001034
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal estrogen use for genitourinary symptoms in women with a history of uterine, cervical, or ovarian carcinoma

Abstract: ObjectiveMenopausal symptoms may adversely affect quality of life and health in women diagnosed with a gynecologic malignancy. The aim of this study was to determine the incidence of adverse outcomes, including cancer recurrence, venous thromboembolism, and secondary malignancies, among patients with a history of endometrial, ovarian, or cervical cancer prescribed vaginal estrogen for genitourinary syndrome of menopause.MethodsA retrospective cohort study was performed including women who were diagnosed with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…5,32,33 Furthermore, a recent study consisting of uterine, cervical, and ovarian cancer patients has shown the safety of vaginal estrogen in these patients, with low risk of recurrence and thromboembolic events. 26 In line with these findings, of the 57 women treated with local or systemic HRT in our study, only 4 women had recurrences. However, fear of HRT in the setting of cancer remains a barrier to acceptance of HRT and was expressed 13 patients in our study, reflecting the importance of patient-provider communication regarding the risks and benefits of HRT.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…5,32,33 Furthermore, a recent study consisting of uterine, cervical, and ovarian cancer patients has shown the safety of vaginal estrogen in these patients, with low risk of recurrence and thromboembolic events. 26 In line with these findings, of the 57 women treated with local or systemic HRT in our study, only 4 women had recurrences. However, fear of HRT in the setting of cancer remains a barrier to acceptance of HRT and was expressed 13 patients in our study, reflecting the importance of patient-provider communication regarding the risks and benefits of HRT.…”
Section: Discussionsupporting
confidence: 88%
“…While there are some systematic and prospective data regarding interventions for sexual dysfunction among cancer populations generally, 23,24 there is little data available to guide this discussion specifically within the realm of pelvic malignancies. While prior studies have focused on the prevalence of sexual changes after PRT [7][8][9][10][13][14][15][16]25 or safety of interventions, 2,6,26 few have focused on efficacy of interventions in improving symptoms. Therefore, in this study, we aimed to describe not only the sexual and menopausal symptoms among female patients with gynecologic and lower gastrointestinal malignancies who underwent PRT, but also treatment patterns and outcomes of patients who were treated in a multidisciplinary program specifically dedicated to these concerns.…”
mentioning
confidence: 99%
“…By extrapolation, it is likely that low-dose intravaginal estrogen is also safe for these women. More recently, a retrospective cohort study concluded that intravaginal estrogen does not appear to increase recurrence risk beyond baseline for women with both early and advanced disease 71 . These findings provide some reassurance about intravaginal low-dose estrogen use in women with either early-stage or even higher-stage endometrial cancers suffering with GSM.…”
Section: Part 1: Intravaginal Estrogenmentioning
confidence: 92%
“…Although data are limited, there is no evidence of increased risk of endometrial cancer recurrence with topical estrogen [60,63]. In contrast, uterine sarcomas may be hormone dependent but there are no clinical trial data to inform practice in women whose tumors are steroid receptor negative [60].…”
Section: Endometrial Cancer and Uterine Sarcomasmentioning
confidence: 99%